Família e autismo: reflexões psicanalíticas com os pais de crianças autistas - Rodrigues, Telma Maria Duarte (2021)
The psychoanalytic clinic of children with autistic spectrum disorder (asd) raises many concerns and questions about the possibilities of clinical management. The initial complaints brought to psychoanalysts by parents and/or guardians indicate the presence of anguish and mourning feelings regarding to the loss of the ideal child, after receiving the diagnosis as well as during the child´s treatment. Therefore, this research aimed to analyze the monitoring of parents during the psychological treatment of their child diagnosed with asd. This is a qualitative, descriptive and documentary research using clinical method. For that, 5 medical records were used, randomly selected, from an interdisciplinary clinic in the east region of são paulo. The medical records referred to children aged between 2 and 10 years old, assisted in the period from 2014 to 2017. The collected material was analyzed from the articulation between the contributions of psychoanalysis and child psychiatry to the autism clinic. The analyzed results indicated that the parents, when narrating, historicizing and subjectifying their stories and the suffering through the diagnosis, enable the autistic child to find a place of desire in their parents. Psychoanalysis, being willing to listen to and welcome the "foreigners", and not eliminating it, enables familiar aspects to produce new meanings about what was presented so strangely. The study made it possible to contribute to clinical and institutional practice aiming at the development of parents´ reinterpretation of their autistic children, promoting new senses of health for the family.(AU)